Hetero–nanostructured Ni/α‐Mn2O3 as Highly Active Catalyst for Aqueous Phase Reduction Reactions. Issue 15 (26th September 2016) - Deka, Pangkita; Sarmah, Pingal; Deka, Ramesh C.; Bharali, Pankaj
Abstract: In this work, a simple strategy for the synthesis of hetero‐nanostructured Ni/α‐Mn2 O3 via surfactant‐aided co‐reduction method is reported. The as synthesized Ni/α‐Mn2 O3 is applied as catalytic material for the aqueous phase reduction of 4‐nitrophenol (4‐NP) and organic dye pollutants, namely Rhodamine B (RhB), Methylene blue (MB), Rose Bengal (RB), Congo red (CR), and Methyl orange (MO) in the presence of a mild reducing agent, NaBH4 . This synthetic route provides homogeneous dispersion of Ni nanoparticles over α‐Mn2 O3 surface. The nanoparticles and support are characterized using XRD, SEM/EDX, TEM, AAS and BET surface area analyses. The Ni particles are spherical, crystalline and size ranges < 5 nm. Further, hetero‐nanostructured Ni/α‐Mn2 O3 is established as a highly efficient recyclable catalyst for the reduction of 4‐NP to 4‐aminophenol (4‐AP). The HPLC and FTIR analysis shows that 4‐AP is the sole product of the reduction of 4‐NP. The Ni/α‐Mn2 O3 also exhibits high activity towards reduction of cationic and anionic dye pollutants. Thus, the as synthesized hetero‐nanostructured Ni/α‐Mn2 O3 can be considered as the future contender for the wastewater treatment. Abstract : We report a simple and efficient synthesis of hetero‐nanostructured Ni/α‐Mn2 O3 via surfactant‐aided co‐reduction method which exhibits high catalytic activity towards aqueous phase reduction of 4‐nitrophenol and dye pollutants.